Spectroscopic investigations of YAG-laser-driven microdroplet-tin plasma sources of extreme ultraviolet radiation for nanolithography. Issue 19 (January 2020) - Versolato, O; Bayerle, A; Bayraktar, M; Behnke, L; Bekker, H; Bouza, Z; Colgan, J; Crespo López-Urrutia, J R; Deuzeman, M J; Hoekstra, R; Kurilovich, D; Liu, B; et al.
Synopsis: Highly charged tin ions are the sources of extreme ultraviolet (EUV) light at 13.5-nm wavelength in laser-produced transient plasmas for next-generation nanolithography. Generating this EUV light at the required power, reliability, and stability however presents a formidable task that combines industrial innovations with challenging scientific questions. We will present work on the spectroscopy of tin ions in and out of YAG-laser-driven plasma and present a surprising answer to the key question: what makes that light?